Effectiveness of antipsychotic medication in patients with schizophrenia in a real world retrospective observational study in Ethiopia - Mulualem Kelebie; Getasew Kibralew; Gebresilassie Tadesse; Gidey Rtbey; Mekidem aderaw; Wondale Endeshaw; Mitiku Belachew; Mulu Muche; Diemesew Getnet; Setegn Fentahun (Scientific Reports)
Abstract Antipsychotic medications have become the cornerstone of treatment for schizophrenia. The antipsychotic drugs are high-affinity antagonists of dopamine D2 receptors that are most effective against psychotic symptoms, but antipsychotic drugs can have side effects that overshadow their advantages, like sedation, extrapyramidal symptoms, and weight gain, which are often experienced as adverse effects. In our country, the relative effectiveness of antipsychotic medication as well as their tolerance in schizophrenia patients is not fully addressed. This study aims to determine the effectiveness of antipsychotic medication and associated factors in schizophrenia patients at the psychiatry clinic. An institutional-based retrospective cohort study was conducted using administrative data of patients with schizophrenia disorder based on the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR) that initiated or changed to a new antipsychotic treatment by clinicians assessments from April 1, 2023, to March 1, 2024 at university of Gondar specialized hospital. The effectiveness of prescribed antipsychotic medication was evaluated using the Clinical Global Impressions-Schizophrenia scale (CGI-SCH), inclusive of subscales for positive, negative, depressive, and cognitive symptoms. A total of 608 patients were receiving antipsychotic medications as follows: 118 patients (19.4%) were prescribed haloperidol, 88 patients (14.5%) were taking chlorpromazine, 48 patients (7.9%) received fluphenazine (decanoate), 126 patients (20.7%) were on risperidone, and 228 patients (37.5%) were treating with olanzapine. In total, 64.8% of patients show improvement in the prescribed medications within one year of treatment (Kaplan-Meier estimate 35.2%) for haloperidol, 31 (26.3%) for chlorpromazine, 30 (34.1%) for Fluphenazine, 19 (39.6%) for risperidone, 51 (40.5%), and 83 (36.4%) for olanzapine. Effectiveness was assessed using the Clinical Global Impressions-Improvement (CGI-I); the overall improvements like negative, positive, depressive, and cognitive symptoms were significantly higher for olanzapine, followed by haloperidol (p < .001). Good adherence (AHR = 0.63; 95% CI 0.5–0.78), history of relapse (AHR = 1.43; 95% CI 1.13–1.82), unemployment (AHR = 1.4; 95% CI 1.06–1.85), and history of suicidal ideation (AHR = 1.79; 95% CI 1.24–2.58) were significant predictors of symptoms improvement. The study found olanzapine is more effective in improving schizophrenia symptoms than other antipsychotic drugs. Medication adherence, symptom relapse, and suicidal thoughts significantly impacted antipsychotic effectiveness in individuals with schizophrenia disorder.